PENGARUH KINERJA LINGKUNGAN DAN LIKUIDITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PADA TAHUN 2018-2023 - M. Agung; Intan Mutiara; Anisa Kurniawati (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to determine the effect of Environmental Performance and Liquidity on Corporate Social Responsibility Disclosure in LQ45 Companies listed on the Indonesia Stock Exchange in 2018 - 2023. The identified population consists of 63 LQ45 companies. The purposive sampling method was used to select the sample, resulting in 9 LQ45 companies as research samples. This study involves observation data for 6 years, namely 2018-2023, with a total of 54 observation data. The secondary data used comes from the annual report for the period 2018-2023 from LQ45 companies listed on the Indonesia Stock Exchange. The approach to this study is quantitative analysis, and various quantitative analysis techniques are used to evaluate the strength of the relationship between the dependent variable and the independent variables in the study. The results of the analysis show that liquidity has a positive effect on CSR disclosure, while environmental performance does not have a significant effect on CSR disclosure. Keywords: Environmental performance, liquidity, Corporate Social responsibility